2018
DOI: 10.1001/jamainternmed.2018.2310
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity or Weight Change With Coronary Heart Disease Among Young Adults in South Korea

Abstract: IMPORTANCE Previous studies have shown a U-or J-shaped association of body mass index (BMI) or change in BMI with coronary heart disease (CHD) among middle-aged and elderly adults. However, whether a similar association exists among young adults is unclear. OBJECTIVE To determine whether an association exists between BMI or BMI change with CHD among young adults. DESIGN, SETTING, AND PARTICIPANTS This population-based longitudinal study used data obtained by the Korean National Health Insurance Service from 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 42 publications
8
82
0
Order By: Relevance
“…Third, the definition of CVD could not be validated by medical records. Although the operational definition for CVD was adopted from previous studies that also used the NHIS database [11,12], future studies with a narrower definition of CVD, perhaps by using procedural codes for cardiovascular interventions or coronary artery bypass grafting operations are needed. Fourth, we could not adjust for certain potential confounders such as education due to the lack of information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the definition of CVD could not be validated by medical records. Although the operational definition for CVD was adopted from previous studies that also used the NHIS database [11,12], future studies with a narrower definition of CVD, perhaps by using procedural codes for cardiovascular interventions or coronary artery bypass grafting operations are needed. Fourth, we could not adjust for certain potential confounders such as education due to the lack of information.…”
Section: Discussionmentioning
confidence: 99%
“…The definition of depression was adapted from another study [10]. CVD was defined when a participant was hospitalized for at least 2 days or died due to CVD, which was adapted from previous studies that used the NHIS database [11,12]. CVD included CHD (ICD-10 codes I20-I25) and stroke (ICD-10 codes I60-I69).…”
Section: Key Variablesmentioning
confidence: 99%
“…A CVD event was defined as 2 or more days of hospitalization or death due to the International Classification of Diseases, Tenth Revision (ICD-10) codes pertaining to CVD. 17,18 Upon admission, the NHIS requires physicians to designate ICD-10 codes for which the patient was hospitalized. Furthermore, causes of death were also determined by ICD-10 codes determined by the attending physician.…”
Section: Key Variablesmentioning
confidence: 99%
“…34 Second, the operational definition of CVD may be prone to misdiagnosis, as evidenced by the unusually higher rate of CHD compared with stroke among men and the low autopsy rate (1.9% of all deaths according to a report in 2013 35 ) in South Korea. Although the operational definition of CVD used in this study has been adopted from multiple previous studies using the same data source, 17,18 future studies that use a more accurate definition of CVD are needed to validate these findings.…”
Section: Limitationsmentioning
confidence: 99%
“…Recently, a longitudinal study of more than 2.5 million young adults in Korea found that overweight and obesity were associated with a higher risk of incident coronary heart disease and that weight gain in those with normal BMI at baseline also significantly increased this risk. 9 Finally, the limitation of BMI as a measure of risk of disease development has recently been highlighted in a study of 296,535 UK Biobank participants, in which other measures of adiposity, including waist circumference, waist to hip ratio, weight to height ratio, and percentage body fat mass, performed better in relation to incident cardiovascular disease risk instead of BMI, the latter often confounded by preexisting comorbidity. 10 This study contributes to our understanding of the risk of AF development in Asian populations.…”
Section: See Also Page 225mentioning
confidence: 99%